Classification of Risks in Tourism - Maksudova U. Sh. (Research Parks Publishers, 2022)
The article examines the existing risks in the activities of the modern international tourism industry, risk factors of a general economic nature and directly related to the consumer of tourism products - the tourist. As a result of the analysis, risk factors were identified and as a result of their identification, a classification of risks related to the tourism sector was formed.